Data from: Life-history characteristics and landscape attributes as drivers of genetic variation, gene flow and fine-scale population structure in Northern Dolly Varden (Salvelinus malma malma) in Canada - Harris, Les N.; Bajno, Robert; Gallagher, Colin P.; Koizumi, Itsuro; Johnson, Lucy K.; Howland, Kimberly L.; Taylor, Eric B.; Reist, James D. (Zenodo, 2016)
The Northern Dolly Varden (Salvelinus malma malma) displays variable life-history types and occupies freshwater habitats with varying levels of connectivity. Here, we assayed microsatellite DNA variation in Northern Dolly Varden from the western Canadian Arctic to resolve landscape and life history variables driving variation in genetic diversity and population structure. Overall, genetic variation was highest in anadromous populations and lowest in those isolated above waterfalls with stream-resident forms intermediate between the two. Anadromous and isolated populations were genetically divergent from each other while no genetic differentiation was detectable between sympatric anadromous and stream-resident forms. Population structure was stable over 25 years, hierarchically organized and conformed to an isolation-by-distance pattern, but stream-isolated forms often deviated from these patterns. Gene flow occurred primarily among Yukon North Slope populations and between sympatric anadromous and resident forms. These results were sex-dependent to some extent, but were influenced more by reproductive status and life history. Our study provides novel insights into the life history, population demographic and habitat variables that shape the distribution of genetic variation and population structure in Arctic fluvial habitats while providing a spatial context for management and conservation. Genepop File This file contains all microsatellite data for all samples/individuals. The year the samples were collected is included as well as the life history type (either freshwater resident (res) or freshwater isolated (iso) forms - note that no code is used for anadromous individuals which constitutes the majority of the samples). Genepop3D-All Samples